Tactile temporalities: The impossible promise of increasing efficiency and eliminating delay through haptic media. (February 2019) - Parisi, David; Farman, Jason
In an attempt to help make humans into more efficient and effective information processors, the engineers of mobile communication systems and devices have turned to touch as an alternative pathway for the transmission of communicative messages. This article traces the goal of using touch as a way to speed up communication from the 1950s experiments with military systems for haptic communication to the launch of the Apple Watch in 2015. Using these two technological milieus as bookends for analyzing the co-constitutive relationship between tactility and temporality, we argue that the ever-accelerating pace of human communication – as seen in the attempts at reducing the latency between sender and receiver through haptic communication – produces bodies that are always on and attentive. Ultimately, the disciplining of time and touch is aimed at the production of neoliberal bodies and information subjects whose skin is utilized as an open channel for attention, communication, and labor. However, as we show by examining the persistence of phantom vibrations and the stalled development of Immersion Corporation's Instinctive Alerts Framework for wearables, the repeated failures of users to properly recognize and differentiate between machine-generated haptic sensations suggest that this attempted transformation of touch into a communicative sense has persistently fallen short of its disciplining aims.